2016
DOI: 10.1177/1476718x14552871
|View full text |Cite
|
Sign up to set email alerts
|

Childcare providers: Work stress and personal well-being

Abstract: Childcare providers face multiple work-related stressors. Small studies of childcare providers have suggested that providers have high levels of depression compared to the general population. However, unlike other caregiving professions, the research examining childcare providers is sparse, and there is little information to inform practices and policies to support childcare providers. This study identifies specific work-related stressors for childcare providers and examines the impact of those work-related st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 24 publications
2
59
0
1
Order By: Relevance
“…In total, 26 articles met the inclusion criteria for health status ( Table 2). Two articles were excluded from the health status analysis because they involved qualitative methods and did not present prevalence estimates [36,37]. The themes from these papers were, however, integrated within the results section.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 26 articles met the inclusion criteria for health status ( Table 2). Two articles were excluded from the health status analysis because they involved qualitative methods and did not present prevalence estimates [36,37]. The themes from these papers were, however, integrated within the results section.…”
Section: Resultsmentioning
confidence: 99%
“…We may want to investigate ways to increase the job control of the lowest income childcare workers, which are typically staff. A qualitative study by Faulkner and colleagues with home-based and center-based child care workers found that common stressors were parental interactions, caregiving, and the failure of public perception to see child care as a profession [54]. Child care workers also reported sleep disruptions (e.g., dreaming about children/work), and physical exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively high rates of turnover and stress, and low rates of employee satisfaction and stability, characterize a variety of professions related to child and family well‐being, including social work, home visiting, child protection, and early childhood education (e.g., Bridges, Fuller, Huang, & Hamre, ; Dillenburger, ; Faulkner, Gerstenblatt, Lee, Vallejo, & Travis, ). Although vastly different in many ways, these fields share important commonalities.…”
Section: Introductionmentioning
confidence: 99%